BASICS OF HOSHIN KANRI. - KESTERSON, RANDY K. (CRC Press, 2017)
The problem with most Hoshin Kanri books is that they describe a complex methodology that is overwhelming to most leaders and their organizations. The need to essentially change the culture of the entire organization to make Hoshin work isn't practical for most companies when first starting out. The Basics of Hoshin Kanri uses an easy-to-follow story format to simplify and explain Hoshin Kanri - a method for strategy deployment. Supplying clear descriptions of the steps of Hoshin Kanri, it advocates using Hoshin as an important tool for improving an organization's existing planning and execution system while simultaneously moving the culture of the organization forward. The book provides readers with a new understanding of Hoshin Kanri as a powerful deployment system for strategic planning, defining a direction and priorities, and aligning the organization around that direction. It begins by telling the story of a manufacturing executive that uses a simple Hoshin Kanri approach to make significant change in his personal life. Next, the book illustrates how this executive prepares to apply Hoshin Kanri to deploy strategy within his business. It concludes by presenting fascinating excerpts from the author's own interviews with experts in the field of Hoshin Kanri. All business leaders want their organizations to be "great" in all respects, but the reality is that they must get to "good" before they can consider becoming "great."